Disrupting Amh and androgen signaling reveals their distinct roles in zebrafish gonadal differentiation and gametogenesis - Kun WU; Yiming YUE; Lingling ZHOU; Zhiwei ZHANG; Hong SHAN; Huanhuan HE; Wei GE (Communications Biology)
Abstract Sex determination and differentiation in zebrafish involve a complex interaction of male and female-promoting factors. While Dmrt1 has been established as a critical male-promoting factor, the roles of Anti-Müllerian hormone (Amh) and androgen signaling remain less clear. This study employed an estrogen-deficient zebrafish model (cyp19a1a-/-) to dissect individual and combined roles of Amh and androgen receptor (Ar) signaling in gonadal differentiation and gametogenesis. Loss of amh, but not ar, could rescue all-male phenotype of cyp19a1a-/-, leading to female or intersex, confirming the role of Amh in promoting male differentiation. This rescue was recapitulated in bmpr2a-/- but not bmpr2b-/-, supporting Bmpr2a as the type II receptor for Amh in zebrafish. Interestingly, while disruption of amh or ar had delayed spermatogenesis, the double mutant (amh-/-;ar-/-) exhibited severely impaired spermatogenesis, highlighting their compensatory roles. While Amh deficiency led to testis hypertrophy, likely involving a compensatory increase in Ar signaling, Ar deficiency resulted in reduced hypertrophy in double mutant males. Furthermore, phenotype analysis of triple mutant (amh-/-;ar-/-;cyp19a1a-/-) provided evidence that Ar participated in early follicle development. This study provides novel insights into complex interplay between Amh and androgen signaling in zebrafish sex differentiation and gametogenesis, highlighting their distinct but cooperative roles in male development.